2020
DOI: 10.1039/c9ee03977e
|View full text |Cite
|
Sign up to set email alerts
|

Exploring new sources of efficiency in process-driven materials screening for post-combustion carbon capture

Abstract: Investigation of adsorbents maximum theoretical performance, computational efficiency of multiscale screening workflows, and consistency of materials rankings for CO2 capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 80 publications
(148 reference statements)
0
80
0
Order By: Relevance
“…In order to identify the operating conditions corresponding to the minimum specific energy and maximum productivity, the 6-step VSA cycle was optimized rigorously using genetic algorithm. Genetic algorithm for VSA optimization is widely studied in literature [35,46,51,52] and we have used the inbuilt multi objective optimization function in Matlab, gamultiobj, which is based on the non-dominated sorting genetic algorithm (NSGA-II) of Deb et al [53].…”
Section: Process Simulation and Optimizationmentioning
confidence: 99%
“…In order to identify the operating conditions corresponding to the minimum specific energy and maximum productivity, the 6-step VSA cycle was optimized rigorously using genetic algorithm. Genetic algorithm for VSA optimization is widely studied in literature [35,46,51,52] and we have used the inbuilt multi objective optimization function in Matlab, gamultiobj, which is based on the non-dominated sorting genetic algorithm (NSGA-II) of Deb et al [53].…”
Section: Process Simulation and Optimizationmentioning
confidence: 99%
“…Although the two differ in just one step, they are known to show measurably different performances 23,24 . While it is certainly possible to construct more complex cycles, we limit ourselves to these two cycles, as they have been used by several research groups as a benchmark 6,8,17,27 , and they have been demonstrated in lab-scale 24 and pilot-scale experiments 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, computational screening modelling strategies are a powerful tool for finding optimum performing materials among thousands of adsorbents, such as MOFs materials. Regarding the vacuum swing adsorption, there is a common relationship between pellet porosity and pellet size for all materials at the optimal adsorbent performance (Farmahini et al 2020). Furthermore, computational simulations could be used for designing new photo-reactive MOFs materials with high adsorption and desorption capacities.…”
Section: Post-combustionmentioning
confidence: 99%